Post-Stroke Cognitive Impairment and Its Association with Quality of Life: A Retrospective Cross-Sectional Study - Kevin Alexander John; Rizaldi Taslim Pinzon (Universitas Airlangga, 2026)
Highlight: Post-stroke cognitive impairment affected over half of ischemic stroke patients. PSCI was not associated with WHOQOL-BREF quality-of-life domains. Post-stroke quality of life is influenced by factors beyond cognitive function. ABSTRACT Introduction: Stroke is a disease that is a major cause of long-term disability and has a significant impact on patients’ quality of life because of cognitive impairment. However, despite the high prevalence of post-stroke cognitive impairment (PSCI), existing evidence on the quality of life (QoL) remains inconsistent, with limited evidence from the Indonesian population. Objective: This study aimed to determine whether cognitive impairments following ischemic stroke are associated with changes in perceived quality of life. Methods: A retrospective cross-sectional study was conducted on 117 ischemic stroke patients at Bethesda Hospital in Yogyakarta. The Mini-Mental State Examination (MMSE) and the Clock Drawing Test (CDT) measured cognitive function, and validated criteria indicated PSCI. Quality of life (QoL) was evaluated using the WHOQOL-BREF, which assesses physical, psychological, social, and environmental domains. The PSCI-QoL associations were analyzed using a chi-square test. Multivariate logistic regression was subsequently used to control for potential confounding variables. A p-value of < 0.05 indicated statistical significance. Result: Post-stroke cognitive impairment was found in 51.7% of patients. Bivariate analysis showed no significant association between cognitive function and quality of life across all WHOQOL-BREF domains, including physical, psychological, social, and environmental. Multivariate logistic regression confirmed the absence of significant associations between PSCI and quality of life across all domains. Conclusion: Post-stroke cognitive impairment was common among ischemic stroke patients but did not affect quality of life across the WHOQOL-BREF domains. These findings emphasize the need for holistic and multidisciplinary post-stroke therapy because physical, psychological, social, and environmental factors influence post-stroke quality of life.